Effects of heme oxygenase-1 on innate and adaptive immune responses promoting pregnancy success and allograft tolerance - Schumacher, Anne; Zenclussen, Ana C. (Frontiers in Pharmacology, 2015)
The heme-degrading enzyme heme oxygenase-1 (HO-1) has cytoprotective, antioxidant and anti-inflammatory properties. Moreover, HO-1 is reportedly involved in suppressing destructive immune responses associated with inflammation, autoimmune diseases, and allograft rejection. During pregnancy, maternal tolerance to foreign fetal antigens is a prerequisite for successful embryo implantation and fetal development. Here, HO-1 has been implicated in counteracting the overwhelming inflammatory immune responses towards fetal allo-antigens, thereby contributing to fetal acceptance. Accordingly, HO-1 ablation negatively impacts the critical steps of pregnancy such as fertilization, implantation, placentation, and fetal growth. In the present review, we summarize recent data on the immune modulatory capacity of HO-1 towards allo-antigens expressed by the semi-allogeneic fetus and organ allografts. In this regard, HO-1 has been shown to promote alloantigen tolerance by blocking dendritic cell (DC) maturation resulting in reduced T cell responses and increased numbers of regulatory T cells. Moreover, HO-1 is suggested to shift the uterine cytokine milieu towards a protective Th2 profile and protects fetal tissue from apoptosis by upregulating anti-apoptotic molecules. Thus, HO-1 is not only a pivotal regulator of the initial steps of pregnancy; but also, an important player in supporting the maternal immune system in tolerating the fetus.